Colonization and infestation ability of Bolboschoenus maritimus Palla in rice paddies of the Camargue, France. Issue 2 (11th June 2013) - Audebert, Alain; Mouret, Jean Claude; Roques, Sandrine; Carrara, Alain; Hammond, Roy; Gaungoo, Azaad; Sanusan, Suchada; Marnotte, Pascal
<x xml:space="preserve">Abstract</x> Bolboschoenus maritimus is one of the major weed constraints for irrigated rice‐cropping systems in the Camargue, France. This perennial plant propagates mainly through the production of numerous tubers. Observations in both controlled conditions and on‐field studies were used to enhance the level of knowledge of the biology, functioning and infestation dynamics of B. maritimus, with a view to rationalize weed control practices. It was found that B. maritimus displayed a great potential to produce a large number of shoots, rhizomes and tubers. Its propagation in the field plots depended on the initial weed density and its spatial colonization did not show any preferred direction (isotropic). Further observations that were made in the paddy fields showed an interaction between the different cultural practices that were tested and the infestation dynamics of B. maritimus. Efficient control of B. maritimus infestation in the field should make use of the data reported here, based on three levels: (i) prevention of weed stem proliferation during the cropping season with specific herbicides; (ii) elimination of the tubers after the rice crop; and (iii) reduction of the tuber‐germinating ability.